Ribbon fish processing value chain in Gujrat: An overview - Renuka V; Ashish Kumar Jha; Toms C Joseph; Ananthan P S (Journal of Indian Fisheries Association, 2022)
Nutritionists all over the world are unanimous in their opinion that fishery resources can meet the protein requirements of the growing population. Fish is considered a cheap high-quality protein that prevents malnutrition in developing countries. The seafood industry provides both food and livelihood to millions of people. Among the marine fish landings, ribbon fishes accounted for the second highest share of 4.46%. However, in terms of value, it was 4.2% at the landing centre and 4.4% at the retail level in 2021. Ribbon fish is generally preferred by the consumer because of its chewy, not too oily, not too fishy meat, and easy to remove bones. It is processed as whole frozen, surimi, dried, and fish meal products. In Gujarat, around 90% of the ribbon fish catch is directly frozen as whole and exported to non-EU countries. Though the ribbon fish plays a major role in the seafood economy of Gujarat, documentation of its nutritional value, processing methods, and quality issues is limited. The present study provides comprehensive knowledge about ribbon fish processing methods and its marketing in Gujarat.